Effects of table tennis participation on balance and postural control in older adults: a systematic literature review - Jeki Haryanto; Dally Rahman; M. Arie Desman (Lentera Negeri, 2026)
It is known that the ability to balance and the control of one's posture tend to worsen as we get older, and as a result, the likelihood of falling, becoming less mobile, and ultimately, losing one's independence increases. Exercise programs that combine physical and mental challenges are now being advised to encourage healthy aging. Table tennis, a sport with a racket but involving low movement, that demands quickness, reflexes, hand-eye coordination, and also a certain degree of balance, has been considered an activity suitable for the elderly; however, the results of its effects are still in pieces. This systematic review was conducted to determine how table tennis impacts balance and postural control as well as other functional outcomes in the elderly. A Scopus search in line with the PRISMA 2020 guidelines yielded 661 records. Screening of titles and abstracts led to the exclusion of 614 articles and after full-text assessment of 47 articles, 40 were excluded leaving seven studies for the eligibility criteria. The studies that were included in this review demonstrated that table tennis, whether as a separate practice, part of multicomponent or exergame programmes, or through the players accumulated playing experience, was associated with improvements in both static and dynamic balance, lessened postural sway, quicker reaction time, better single-leg stance performance, and greater functional mobility. Other advantages were improved sensorimotor connectivity, better quality of life, and increased antioxidant levels. Though the studies reviewed were small in number and diverse in methodology, the results show that table tennis is a highly effective, low-risk way of helping older adults maintain their balance and postural control.